Modeling and Simulation of 27- Level Hybrid H-Bridge Multilevel Inverter for PV System (International Journal of Engineering and Computer Science, 2018)
In this paper, modeling of photovoltaic array and hybrid H-bridge multilevel inverter is done using latest algorithm techniques in order to improve the performance of the PV system and decrease the complexity and total cost of the inverter. Here MPPT algorithm is used for extracting the maximum power from the solar PV module and transferring that power to the load by varying the duty cycle. Among MPPT algorithm techniques, incremental conductance method can perform maximum power point tracking under rapidly varying irradiation conditions with higher accuracy than the perturb and observe method .A hybrid H-bridge multilevel inverter is preferred over all other topologies as it requires less number of switches by which high number of voltage levels are obtained and also reduced THD. The modeling and simulation for the above systems is performed in MATLAB and the generated output voltage is analyzed